A Comparative Study between Printed and Digital Publication: Identifying digital natives' preference towards their purchasing decisions - Joselito C. Bolinao Jr, Camille R. Merano, Claudie R. Papa, Joshua Renaldee L. Salcedo, John Patrick S. Santos, and Marcis Roce C. Victor. 4 0 16; 5
u
Business Research (BSBA major in Marketing Management) Pamantasan ng Lungsod ng Maynila, 2015.
Keywords: 2 -- 0; 6; 20; 20; 2